A General Approach to Shaped MOF‐Containing Aerogels toward Practical Water Treatment Application. (12th May 2020) - Cheng, Ping; Kim, Minjun; Lim, Hyunsoo; Lin, Jianjian; Torad, Nagy L.; Zhang, Xiaogang; Hossain, Md. Shahriar A.; Wu, Chia‐Wen; Wang, Chaohai; Na, Jongbeom; Yamauchi, Yusuke
Abstract: Porous materials are widely studied for water purification and treatment as they can function as efficient adsorbents for harmful chemical wastes with their high specific surface areas. Among various types of porous materials, metal‐organic frameworks (MOFs) have emerged as promising adsorbents for organic pollutants although the general powder form of MOFs largely limits their recyclability in practical applications. Herein, highly crystalline MOF particles are incorporated into agarose (AG) to fabricate highly recyclable MOF aerogels. Along with greatly improved recyclability, these MOF aerogels also achieve eco‐friendliness and cost‐effectiveness because AG is highly abundant in nature and can be easily modified. Typically, MOF aerogels are synthesized by uniformly dispersing MOF particles into the AG solution. The resulting MOF aerogels show significantly improved efficiency for dye adsorption. It is believed that this fabrication method for the preparation of MOF aerogels is highly versatile and it can be extended to other types of MOFs for different applications including environmental remediation, energy storage and conversion, and sensing. Abstract : Eco‐friendly and cost‐effective metal‐organic framework (MOF)‐containing aerogel composites are synthesized with agarose by using a facile method. The synthesized MOF aerogels show high efficiency for dye adsorption that is related to water treatment applications, through their large surface area and high MOF dispersibility in aerogel.